Mycobacterium tuberculosis Specific Protein Rv1509 Evokes Efficient Innate and Adaptive Immune Response Indicative of Protective Th1 Immune Signature - P, Manjunath; Ahmad, Javeed; Samal, Jasmine; Sheikh, Javaid Ahmad; Arora, Simran Kaur; Khubaib, Mohd; Aggarwal, Heena; Kumari, Indu; Luthra, Kalpana; Rahman, Syed Asad; Hasnain, Seyed E.; Ehtesham, Nasreen Z. (Frontiers in Immunology, 2021)
Dissecting the function(s) of proteins present exclusively in Mycobacterium tuberculosis (M. tb) will provide important clues regarding the role of these proteins in mycobacterial pathogenesis. Using extensive computational approaches, we shortlisted ORFs/proteins unique to M. tb among 13 different species of mycobacteria and identified a hypothetical protein Rv1509 as a ‘signature protein’ of M. tb. This unique protein was found to be present only in M. tb and absent in all other mycobacterial species, including BCG. In-silico analysis identified numerous putative T cell and B cell epitopes in Rv1509. Initial in vitro experiments using innate immune cells demonstrated Rv1509 to be immunogenic with potential to modulate innate immune responses. Macrophages treated with Rv1509 exhibited higher activation status along with substantial release of pro-inflammatory cytokines. Besides, Rv1509 protein boosts dendritic cell maturation by increasing the expression of activation markers such as CD80, HLA-DR and decreasing DC-SIGN expression and this interaction was mediated by innate immune receptor TLR-2. Further, in-vivo experiments in mice demonstrated that Rv1509 protein promotes the expansion of multifunctional CD4+ and CD8+ T cells and induces effector memory response along with evoking a canonical Th1 type of immune response. Rv1509 also induces substantial B cell response as revealed by increased IgG reactivity in sera of immunised animals. This allowed us to demonstrate the diagnostic efficacy of this protein in sera of human TB patients compared to the healthy controls. Taken together, our results reveal that Rv1509 signature protein has immunomodulatory functions evoking immunological memory response with possible implications in serodiagnosis and TB vaccine development.